Manusia Dalam Perspektifal-Qur'an Kajian Pendidikan Islam - Rahmana, Sitto (CV. ITTC INDONESIA, 2022)
Humans as the most perfect creatures created by Allah SWT place humans as servants of Allah and the caliph of Allah fi al-ardh who are tasked and responsible for prospering life on earth in accordance with Allah's commands. To prepare the next generation of the caliphate in accordance with religious values, humans need to get a good education. The purpose of this article is to describe humans in the perspective of the Qur'an in the study of Islamic religious education. With information analysis method with content analysis approach (content analysis). In the Qur'an, humans are referred to by several terms, namely: al-Insan, al-Ins, al-Basyar, Bani Adam and an-Nas. All human terms mentioned in the Qur'an have various potentials and characteristics inherent in each human being. Therefore, in order for all the potential possessed by humans to be better directed, it needs to be fostered and developed as a whole to achieve perfection through a good and correct educational process.